2017
DOI: 10.1021/acs.jmedchem.7b01199
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Aromatic Carbamates that Confer Neuroprotective Activity by Enhancing Autophagy and Inducing the Anti-Apoptotic Protein B-Cell Lymphoma 2 (Bcl-2)

Abstract: Neurodegenerative diseases share certain pathophysiological hallmarks that represent common targets for drug discovery. In particular, dysfunction of proteostasis and the resultant apoptotic death of neurons represent common pathways for pharmacological intervention. A library of aromatic carbamate derivatives based on the clinically available drug flupirtine was synthesized to determine a structure–activity relationship for neuroprotective activity. Several derivatives were identified that possess greater pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 50 publications
1
41
0
Order By: Relevance
“…It is generally believed that cell death may involve necrosis, apoptosis and autophagy, and the balance between apoptosis and autophagy plays an important role in cell survival. 44,45 Besides ROS-induced cell necrosis, apoptosis and autophagy are also important in cell death in IR. Apoptosis is related to the severity of ischemia and the time of reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally believed that cell death may involve necrosis, apoptosis and autophagy, and the balance between apoptosis and autophagy plays an important role in cell survival. 44,45 Besides ROS-induced cell necrosis, apoptosis and autophagy are also important in cell death in IR. Apoptosis is related to the severity of ischemia and the time of reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…31 Moreover, autophagy showed an increase in the expression of autophagy-related proteins such as LC3-II, Beclin-1, and ATG5, with a decrease in the expression of p62. 32 Kinarivala et al 33 reported that the activated Beclin-1 could induce autophagy. In this study, we investigated the effect of Genipin on autophagy in OSCC for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Intrathecal injection of TPP1 slows down CLN2 disease in mice and humans. Flupirtine and aromatic carbamate derivatives antiapoptotic properties provide the basis for use as potential therapies in NCL disease.…”
Section: Introductionmentioning
confidence: 99%